Eficiência nutricional e acúmulo de nutrientes em genótipos de pitaya - Saraiva, José Laylton Rogério (2024)
The cultivation of pitaya (Selenicereus spp. syn Hylocereus spp.) has been gaining prominence in both domestic and international markets, establishing itself as an excellent income-generating alternative for rural areas. Recently, the first pitaya genotypes developed specifically for Brazil were launched; however, there remains a lack of information regarding the field management of this fruit crop, particularly concerning its nutritional requirements and the accumulation of essential elements in the plant during its development. Thus, the objective was to evaluate the efficiencies of nutrient absorption, transport, and utilization, as well as the nutrient accumulation in pitaya genotypes under tropical conditions in the coastal region of Ceará. The experiment was conducted in a randomized block design with six treatments (genotypes), six replications, and three plants per plot, totaling 108 plants. The genotypes studied were 'BRS Âmbar do Cerrado' (S. megalanthus), 'BRS Minipitaya do Cerrado' (S. setaceus), 'BRS Luz do Cerrado' (H. undatus), 'BRS Lua do Cerrado' (H. undatus), 'BRS Granada do Cerrado' (H. undatus X H. costaricensis), and a control genotype, a red pitaya (H. costaricensis) commonly used by local producers. Dry matter mass, nutrient accumulation, and nutritional efficiencies were determined 220 days after planting (DAP). The pitaya genotypes showed differences in nutrient absorption, transport, and utilization efficiency, as well as in nutrient and sodium accumulation. The 'Granada do Cerrado' genotype exhibited the highest dry matter production (171.73 g/plant), while the 'Âmbar do Cerrado' genotype had the lowest production (23.27 g/plant). The costaricensis and 'Âmbar do Cerrado' genotypes were more efficient in nutrient and sodium absorption and transport. The 'Granada do Cerrado' genotype was the most efficient in nutrient and sodium utilization. The genotypes displayed the following descending order of nutrient accumulation: K > Ca > N > Mg > P > S > Na > Zn > Mn > B > Fe > Cu, with some exceptions. For the 'Âmbar do Cerrado' genotype, the order of micronutrients was Fe > Mn > Zn > B > Cu, and for the 'Minipitaya do Cerrado' genotype, the order was Fe > B > Cu. The 'Luz do Cerrado' genotype accumulated more N than Ca.